Mutation distribution in the von Willebrand factor gene related to the different von Willebrand disease (VWD) types in a cohort of VWD patients - Yadegari, Hamideh; Driesen, Julia; Pavlova, Anna; Biswas, Arijit; Hertfelder, Hans-Jörg; Oldenburg, Johannes (Thrombosis and Haemostasis, 2012)
Von Willebrand disease (VWD) is the most common inherited bleeding disorder caused by quantitative or qualitative defects of the von Willebrand factor (VWF). VWD is classified into three types – type 1 (partial quantitative deficiencies), type 2 (qualitative defects) and type 3 (complete deficiency of VWF). In this study we explored genotype and phenotype characteristics of patients with VWD with the aim of dissecting the distribution of mutations in different types of VWD. One hundred fourteen patients belonging to 78 families diagnosed to have VWD were studied. Mutation analysis was performed by direct sequencing of the VWF. Large deletions were investigated by multiplex ligation-dependent probe amplification (MLPA) analysis. The impact of novel candidate missense mutations and potential splice site mutations was predicted by in silico assessments. We identified mutations in 66 index patients (IPs) (84.6%). Mutation detection rate was 68%, 94% and 94% for VWD type 1, 2 and 3, respectively. In total, 68 different putative mutations were detected comprising 37 missense mutations (54.4%), 10 small deletions (14.7%), two small insertions (2.9%), seven nonsense mutations (10.3%), five splice-site mutations (7.4%), six large deletions (8.8%) and one silent mutation (1.5%). Twenty-six of these mutations were novel. Furthermore, in type 1 and type 2 VWD, the majority of identified mutations (74% vs. 88.1%) were missense substitutions while mutations in type 3 VWD mostly caused null alleles (82%). Genotyping in VWD is a helpful tool to further elucidate the pathogenesis of VWD and to establish the relationship between genotype and phenotype.
Keywords: VWF mutations; von Willebrand disease; VWD phenotype; VWD types; VWF A1 domain